2014
DOI: 10.1109/jphot.2014.2302791
|View full text |Cite
|
Sign up to set email alerts
|

All-Optical OFDM Generation for IEEE802.11a Based on Soliton Carriers Using Microring Resonators

Abstract: The optical carrier generation is the basic building block to implement all-optical orthogonal frequency-division multiplexing (OFDM) transmission. One method to optically generate single and multicarriers is to use the microring resonator (MRR). The MRRs can be used as filter devices, where generation of high-frequency (GHz) soliton signals as single and multicarriers can be performed using suitable system parameters. Here, the optical soliton in a nonlinear fiber MRR system is analyzed, using a modified add/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The ability of chaotic carriers to synchronize in a communication system is valid. Recently, Amiri et al have reported the successful experimental research based on generating and transmission of chaotic signals using an optical fiber communication link [29,30,83]. They proposed a system for chaotic signal generation and cancellation using a MRR fiber optic system, where the required signals of single bandwidth soliton pulse are recovered and manipulated using an add/drop system.…”
Section: Ring Resonatorsmentioning
confidence: 99%
“…The ability of chaotic carriers to synchronize in a communication system is valid. Recently, Amiri et al have reported the successful experimental research based on generating and transmission of chaotic signals using an optical fiber communication link [29,30,83]. They proposed a system for chaotic signal generation and cancellation using a MRR fiber optic system, where the required signals of single bandwidth soliton pulse are recovered and manipulated using an add/drop system.…”
Section: Ring Resonatorsmentioning
confidence: 99%
“…Referring to Fig. 1, the equations of the modified add/drop system are given by the following [22,23]:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…We also assume that the PUs transmit on K separate channels such that each PU k transmits on one single channel number k ( k ∈{1, …, K }). This assumption is easily applicable in any Orthogonal Frequency Division Multiple Access‐based primary network (e.g., ). On the other hand, all PUs have the same transmit power pkPU and all SUs have equal transmit power p too.…”
Section: System Modelmentioning
confidence: 99%